Three new species of Nazeris Fauvel from the Jiuwan Mountain, Guangxi, China (Coleoptera, Staphylinidae, Paederinae) - Li, Xin-Meng; Wu, Wei-Ping; Hu, Jia-Yao (Zootaxa, 2023)
Three new species of Nazeris Fauvel, 1873 from the Jiuwan Mountain, Guangxi, China, are described and illustrated: N. jiuwanensis, sp. n., N. qingshuius, sp. n. and N. yangmeius sp. n. An identification key to the Nazeris species in Guangxi is provided.